2017
DOI: 10.1021/acsami.7b15264
|View full text |Cite
|
Sign up to set email alerts
|

BN Nanosheet/Polymer Films with Highly Anisotropic Thermal Conductivity for Thermal Management Applications

Abstract: The development of advanced thermal transport materials is a global challenge. Two-dimensional nanomaterials have been demonstrated as promising candidates for thermal management applications. Here, we report a boron nitride (BN) nanosheet/polymer composite film with excellent flexibility and toughness prepared by vacuum-assisted filtration. The mechanical performance of the composite film is highly flexible and robust. It is noteworthy that the film exhibits highly anisotropic properties, with superior in-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
148
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(152 citation statements)
references
References 54 publications
2
148
2
Order By: Relevance
“…[128] By vacuum-assisted filtration (VAF) Yuanpeng Wu and coworkers fabricated BN/PDDA nanocomposite with excellent flexibility and toughness. [129] Facile vacuumassisted filtration method was adopted by Xiaoliang Zeng et al for the preparation of cellulose nanofiber (CNF)/ BNNT nanocomposites with promising applications in thermal interface materials, printed circuit boards or organic substrates in electronics. [130] PCL/BNNP nanocomposites were synthesized by Li Hao and coworkers using co-precipitation technique.…”
Section: Other Methodsmentioning
confidence: 99%
“…[128] By vacuum-assisted filtration (VAF) Yuanpeng Wu and coworkers fabricated BN/PDDA nanocomposite with excellent flexibility and toughness. [129] Facile vacuumassisted filtration method was adopted by Xiaoliang Zeng et al for the preparation of cellulose nanofiber (CNF)/ BNNT nanocomposites with promising applications in thermal interface materials, printed circuit boards or organic substrates in electronics. [130] PCL/BNNP nanocomposites were synthesized by Li Hao and coworkers using co-precipitation technique.…”
Section: Other Methodsmentioning
confidence: 99%
“…It was found that the thermal conductivity of silk can be improved by increasing the crystallinity of silk proteins, although it is still much lower than many inorganic materials [24][25][26]. On the other hand, boron nitride (BN) nanomaterials have excellent thermal stability, thermal conductivity, and stable chemical properties, and have long-term good insulation properties [27][28][29][30]. Cell and animal experiments have also shown that boron nitride is not cytotoxic in the proper dosage range and does not have any negative effects on animal signs, which indicates that boron nitride is also biocompatible [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR spectra of dried h‐BN, HPC, and GF are shown in Figure . The two strong characteristic absorption peaks of h‐BN can be attributed to the B‐N stretching vibrations at around 1374 cm −1 and blending vibration at around 818 cm −1 . For HPC, the broad peak from 3700 cm −1 to 3100 cm −1 is associated with the presence of hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%